PENGARUH SOCIAL SUPPORT, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA MAKARONIMU MADIUN (OUTLET KECAMATAN DOLOPO) - Pradana, Sepbrio Ian; Santoso, Adi; Purwaningrum, Titis (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This research is intended to be able to see partially and simultaneously whether purchasing decisions at Makaronimu Madiun (Dolopo District Outlets) are influenced by social support, product quality, and location. Because at this time in the business world there is always intense competition, so you have to be able to correct those that occur as a result of various problems and be more sensitive in order to maintain and develop your business. The current research applies a quantitative method that uses important information by distributing it to 100 people. The sampling method used by researchers is non-probability sampling with accidental sampling. The analysis used in this study applies multiple linear regression analysis through processing the SPSS 26 application. The conclusion of this study shows that the partial test (t) consists of Social Support (X1) = 0.000, Product Quality (X2) = 0.005, and Location (X3) ) = 0.000.